Bài giảng Tiếng Anh chuyên ngành Quản trị kinh doanh - NGUYỄN, VĂN CHUNG (Khoa Kinh tế- Du lịch, 2021)
P resent contents:Managerment as Managerment, managing across cultures,work and motivation,....; Production as The difference sectors of the economy, Production, logistics,...